Peranan Internal Audit dalam Meningkatkan Pengendalian Intern Piutang : Studi Kasus pada PT. Vaksindo Satwa Nusantara - Pamungkas, Bambang (Jurnal Ilmiah Ranggagading (JIR), 2005)
Internal Audit in optimizing control of internal credit is implemented in line with the fixed procedure determined by the company. The main reason why a company gives credit facility is in order to attract the consumers so that the volume of sales is increased, and therefore the business keeps running. Selling on credits does not generate cash soon but it generates credit from the consumers and when the date is due, cash flow is generated. The role of Internal audit really supports the control of internal credits carried out in determining the collection of credit from the consumers as well as maintaining the stability of cash flow determined by the fixed procedure implemented in controlling internal credits so that the business runs effectively and efficiently. Key words: Internal Audit; Controlling Internal Credits.